Characterization of Ngef, a novel member of the Dbl family of genes expressed predominantly in the caudate nucleus. - Rodrigues, N; Theodosiou, A; Nesbit, M; Campbell, L; Tandle, A; Saranath, D; Davies, K (2000)
We have identified Ngef as a novel member of the family of Dbl genes. Many members of this family have been shown to function as guanine nucleotide exchange factors for the Rho-type GTPases. Ngef is predominantly expressed in brain, with the strongest signal in the caudate nucleus, a region associated with the control of movement. Ngef contains a translated trinucleotide repeat, a polyglutamic acid stretch interrupted by a glycine. We have localized the Ngef gene to mouse chromosome 1 and the human homologue of Ngef to human chromosome 2q37. We have shown in preliminary experiments that Ngef has transforming potential in cell culture and is able to induce tumors in nude mice.